Modeling packaging machine systems on the basis of proportional pressure regulator - Kryvoplias-Volodina, Liudmyla (My University, 2016)
The vertical multithreading packaging machines that work with two rolls, usually used for packaging melkoportsionnogo granular, liquid, paste and small-piece products in flat chetyrehshovnye packages manufactured from a variety of heat-sealable or heat sealable film materials, as well as filtrobumagi, polyethylene laminated paper and aluminum foil. Thus the opposing surfaces of such packets may be made of different materials. When forming the package is necessary to provide a pressure control system of the tension roll materials. As a control device, consider the use of MX PRO proportional pressure regulator in the automatic control system. The important problem in the operation of automatic control systems (ACS), the gas pressure is required to ensure the dynamic quality and, above all, lack of self-oscillating uncontrolled processes that reduce the service life of systems and precision gas flow measurement
Keywords: vertical multithreading packaging machines; small-piece products; штучна продукція; proportional pressure regulator; пропорційний регулятор тиску